Green Tourism Planning for Coastal Development in Gunungsewu Geopark, Indonesia - Soeroso, A. (Association for Geoinformation Technology, 2023)
Having spectacular views of the karst landscape area, Gunungsewu Geopark (GG) has increasingly become a popular tourist area in the southern part of Java Island, Indonesia. With a significant increase in tourist visits and tourism development along the beaches area, the fragile environment of GG is severely threatened. This study aims to propose a design of green tourism planning in the coastal area of GG. We collected data through in-depth interviews, brainstorming, expert meeting, and focus group discussions with the key informants representing all stakeholders. The results show that GG could be grouped into two clusters to develop coastal green tourism namely cluster 1 that can be developed as public tourism and cluster 2 that can be focused on natural landscape preservation. Furthermore, seven recommendations are proposed to be carried out in the future in order to develop sustainable tourism in GG. © Geoinformatics International.